Palliative Care Issues and Challenges in Saudi Arabia: Knowledge Assessment Among Nursing Students. Issue 3 (July 2017) - Khraisat, Omar Mohammad; Hamdan, Mahmoud; Ghazzawwi, Mohannad
Background: Nurses are the heart of the palliative care team who provide high standards of care since they spend the longest time with patients. However, lack of adequate knowledge of palliative care is considered as one of the main obstacles to palliative care improvement. Aim: A survey was conducted to assess Saudi nursing students' knowledge about palliative care. Methods: Using a descriptive design, 154 students who enrolled in first year and who will graduate within 1 year were surveyed in a nursing college located in Riyadh, the capital of Saudi Arabia. The Palliative Care Quiz for Nursing (PCQN) was used to assess students' knowledge. Results: The sample mean age was 22.1 (standard deviation (SD): 2.2), and most of the students were predominately female (93; 60.4%) and the majority were senior students who will be graduated within the current academic year (105; 68.2%). The total mean score of palliative care knowledge was low at 7.30 (SD: 0.56; range: 0-13), and the number of correctly answered statements ranged from 16 (10.4%, statement no. 7) to 91 (59.1%, statement no. 18). Eleven misconceptions about palliative care among participants are conceptually categorized into 3categories: principle and philosophy of palliative care, pain and symptom management, and psychological and spiritual care. Conclusion: Integrating palliative care education within the nursing programs is the backbone to improve nursing students' knowledge, namely, in principles of palliative care and symptom management.